A physicalist manifesto : thoroughly modern materialism - Melnyk, Andrew (Cambridge University Press, 2003)
A Physicalist Manifesto is a full treatment of the comprehensive physicalist view that, in some important sense, everything is physical. Andrew Melnyk argues that the view is best formulated by appeal to a carefully worked-out notion of realization, rather than supervenience; that, so formulated, physicalism must be importantly reductionist; that it need not repudiate causal and explanatory claims framed in non-physical language; and that it has the a posteriori epistemic status of a broad-scope scientific hypothesis. Two concluding chapters argue in detail that contemporary science provides no significant empirical evidence against physicalism and some considerable evidence for it. Written in a brisk, candid and exceptionally clear style, this 2003 book should appeal to professionals and students in philosophy of mind, metaphysics and philosophy of science.